Digital agricultures as a dispute space: towards new agronomic imaginations in the global south - Carrozza, Tomás Javier (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In recent years, digital agricultures (AD) have taken a central role in discussions about food productive models. Thus, a mutation is attended in the way of understanding agri -food systems and agronomy, as a disciplinary field, is increasingly conceptualized as a space of "technological management."In this way, technological intermediations are increasingly relevant and attends an increasingly profound "box" between each of the stages in which food is produced.In a context of deepening of extractive logic in agriculture, AD placed in front of a second extraction process, that associated with data and crop management by generating standardized processes for agricultural production. Faced with this context, the processes of appropriation of speeches and knowledge by the hegemonic actors of the agri -food sector are increasingly strong.However, from the Global South a space of dispute and dialogue that seeks to rethink ad senses as emancipation and technological sovereignty begins to be constituted.In this scenario, the objective of this work is to analyze the characteristics of those experiences that propose to build an ad "alternative" and how these translate into the context of epistemic and ontological discussions about agronomy. In this way, AD and their reappropriation can become a space for disciplinary transformation that would lead to Imagine the processes of knowledge mobilization and decolonization of productive systems.